Internal and External Determinants of Economic Growth: A closer look at Pakistan’s Economy - Muhammad Jamil; Rao Muhammad Atif; Khalid Zaman (Romanian Economic Journal, 2013)
This study aims to investigate the impact of internal and external determinants of economic growth on the economic growth of Pakistan. Major internal determinants include stock of physical capital and developmental expenditures, while external determinants include trade openness and real effective exchange rate. In doing so, study utilizes the annual time series data from 1972 to 2011. Advanced Autoregressive Distributed Lag model (ARDL) approach has been employed for co-integration and error correction model (ECM) for short-run results. Empirical investigations indicate that developmental expenditures, physical capital and trade openness are positively correlated with economic growth in long run, while real effective exchange rate negatively and significantly affect economic growth in long run in case of Pakistan.